PERTAPAAN PADA MASA BALI KUNO ABAD IX-XII MASEHI - Ni Made, Dewi Wahyuni (Humanis, 2015)
At the time of ancient Bali between the 9 th to 12 th centuries AD, it was mentioned of the term “hermitage” in the inscription. Hermitage became a very important thing in people's lives in the past so that hermitage was cited in several inscriptions of the period. The issues discussed in this study arewhat the physical forms of hermitage found to date in Bali as well as the function of the h ermitage building in the past and how the role of the hermitage people based on the inscriptions of ancient Bali of the 9 th to 12 th centuries A D . Thepurpose of this study are to reconstruction religious of the ancient Bali community from hermitage building and to answer the problems of the research . This study is a qualitative research, namely research that promotes the quality of the data and analyzed in order to reach the target depth, descriptive research results presented in the form of words and language. The results of this research are the form of hermitage found in Bali in general is in the form of cave and niche hermitages. The cave hermitages are located in Goa Gajah and Goa Patinggi. While the niche-shaped hermitage were found at Temple of Tebing Gunung Kawi, Temple of Kerobokan, Tebing Tegallinggah Temple, Goa Garbha, Kelebutan Temple, Temple of Jukut Paku, Relief of Bebitera, Relief of Yeh Pulu, and in Pura Telaga Waja . The function of building the h ermitageis a religious holy building to perform religious ceremonies or to meditate , the abode of the hermit as well as a dormitory for the teaching and learning process. the servants on duty at the Hermitage area during ancient Bali of IX-XII centuries AD mentioned in inscriptions as samgat wilang patapan dan samgat tapa haji .
Keywords: Hermitage, Form and Function, Hermitage’s servants